Answer:
The function g(x) has a greater value when x = 3. The function g(x) will be 7 when x = 3 while the function f(x) is will be 5
Explanation:
For the function f(x), when x = 3, you get the equation f(x) = 2(3) - 1. Two times three equals six, so the equation can be simplified to f(x) = 6 - 1. Six minus one equals five, so f(x) = 5 when x = 3.
For the function g(x), when x = 3, you get the equation g(x) = 4(3) - 5. Four times three equals 12, so the equation is now g(x) = 12 - 5. 12 minus five equals seven, so g(x) = 7 when x = 3.
Hope this helps :)